Matrix Approach for Modeling the Interrelationships of Business Processes and Organizational Structure of an Educational Institution - E. A. Bushchyk; N. I. Listopad (Цифровая трансформация)
The complex model describing and taking into account the interrelationships between business processes, organizational structure and information systems of a secondary special education institution is considered. To represent the model the matrix approach with the use of matrix theory tools is used. Weight coefficients of   interrelation of model elements are described using the method of expert evaluation and taking into account the zone of responsibility of employees in the performance of certain business processes. The model construction is based on the description of the operational business process “Training of specialists at the level of secondary specialized education”, including subprocesses of theoretical and practical training. The obtained model, consisting of three matrices, allows for accounting and analysis of organizational elements of the educational institution structure for  errors, assessment of completeness and cohesion of interaction between structures in order to their further optimization and  automation.